MODERNIZATION OF CUPOLA EQUIPMENT - S. L. Rovin (Litʹë i Metallurgiâ, 2016)
This article presents an automated cupola complex, developed by scientific-production enterprise «Technolit» together with GSTU named after P. O. Sukhoi, launched in the spring of 2015 at the plant «Stroiex» in the city of Chelyabinsk (the Russian Federation). The old cupolas (open type) have been replaced by the new cupolas of the closed type, equipped with automatic control and management system and multistage wet gas treatment system. Cupolas are equipped with systems of post-combustion gases and the batch charging, the separate systems of air blast, systems of sludge removal and recirculation of water, the slag granulation installations, mechanized cleaning of cupola furnace and automatic safety system. These activities allowed the company to increase production and improve the quality of cast iron, reduce the coke consumption by 20% and reducing emissions of pollutants into the atmosphere almost 30 times.